2005
DOI: 10.1246/cl.2006.88
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecular Morphology of Porphyrin/DNA Complex

Abstract: A Porphyrin/DNA complex stabilized by both ionic bonds and stacking of conjugates is reported herein. Morphology observation on the single molecular level revealed that the complex exhibits rigid behavior and inhomogeneity with phase separation. These characteristics are the indication of the presence of stacking interaction between porphyrins along the DNA scaffold.One-dimensional molecular complexes are attracting much interest for the design of nanostructured materials with electronic and magnetic functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The intensity decreases for l > 1.7 and increases again for l < 1.7, while no isosbestic point is observed. This indicates that the system cannot be described by a simple equilibrium of two spectroscopically distinguishable species, as it is often the case for dye molecules binding to polyelectrolytes where monomeric and (bound) stacked dye molecules are in equilibrium. , The result is also in difference to UV−vis properties of meso-tetrakis(4- N -methylpyridiumyl) porphyrin (TMPyP) that interacts with DNA by intercalation, , but rather in some similarity with meso-tetrakis(4-( N -trimethylammonium)-phenyl)porphyrin (TAPP) , or meso-tetrakis(4- N -ethylpyridiumyl)-porphyrin (TEPyP) that bind outside at the DNA surface. No mutual π−π interaction of PSPDI is induced upon binding to DNA, as expected for a molecular geometry with bulky groups surrounding the aromatic system.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity decreases for l > 1.7 and increases again for l < 1.7, while no isosbestic point is observed. This indicates that the system cannot be described by a simple equilibrium of two spectroscopically distinguishable species, as it is often the case for dye molecules binding to polyelectrolytes where monomeric and (bound) stacked dye molecules are in equilibrium. , The result is also in difference to UV−vis properties of meso-tetrakis(4- N -methylpyridiumyl) porphyrin (TMPyP) that interacts with DNA by intercalation, , but rather in some similarity with meso-tetrakis(4-( N -trimethylammonium)-phenyl)porphyrin (TAPP) , or meso-tetrakis(4- N -ethylpyridiumyl)-porphyrin (TEPyP) that bind outside at the DNA surface. No mutual π−π interaction of PSPDI is induced upon binding to DNA, as expected for a molecular geometry with bulky groups surrounding the aromatic system.…”
Section: Resultsmentioning
confidence: 99%
“…Going around the perimeter, it is observed that the structure is made up of several strands or threads that in some regions join to form a compact and uniform strand that is darker than the rest with diameters between 4.5 and 10 μm. Interestingly, these compact strands can be fully stretched as at the top or forming "random coil" 35 -type structures as seen on the left side (see Figure S1). On the right side of the structure, we observe that the compact strand loses its homogeneity, and the constituent strands "open" or disperse to form ovoid structures that close at the other end to continue with the compact strand.…”
Section: ■ Introductionmentioning
confidence: 99%

DNA Hyperstructure

León-Paz-de-Rodríguez,
Rodríguez-León,
Iñiguez-Palomares
2024
ACS Omega